Thornado-hydro: towards discontinuous Galerkin methods for supernova hydrodynamics 1This manuscript has been authored by UT-Battelle, LLC under Contract No. DE-AC05-00OR22725 with the U.S. Department of Energy. The United States Government retains and the publisher, by accepting the article for publication, acknowledges that the United States Government retains a non-exclusive, paid-up, irrevocable, world-wide license to publish or reproduce the published form of this manuscript, or allow others to do so, for United States Government purposes. The Department of Energy will provide public access to these results of federally sponsored research in accordance with the DOE Public Access Plan (http://energy.gov/downloads/doe-public-access-plan). (May 2019) - Endeve, Eirik; Buffaloe, Jesse; Dunham, Samuel J; Roberts, Nick; Andrew, Kristopher; Barker, Brandon; Pochik, David; Pulsinelli, Juliana; Mezzacappa, Anthony
Abstract: The toolkit for high-order neutrino-radiation hydrodynamics (thornado) is being developed for simulations of core-collapse supernovae (CCSNe) and related problems. Current capabilities in thornado include solvers for the Euler equations — in non-relativistic and special relativistic limits — and the two-moment model of neutrino transport. The spatial discretization in thornado is based on the discontinuous Galerkin (DG) method, which is receiving increased attention from the computational astrophysics community. In this paper, we provide an overview of the numerical methods for the Euler equations in thornado, and present some encouraging preliminary numerical results from a set of basic tests in one and two spatial dimensions.